Strategi pemasaran produk unggulan BUMDes berbasis digital - Andrias U. T. Anabuni; Septiana Sakalini; Yessi S. I. P. Benu; Margaretha Margaretha; Irminda L. Dewiaty; Maria S. L. Kelen; Amram R. Bire; Marianus H. Sanga; Hairil Nurdin; Irience R. A. Manongga (Nur Science Institute, 2026)
This community service program aims to formulate digital marketing strategies to promote and sell superior BUMDes products. The methods employed include socialization, training, and mentorship using a participatory action research approach that emphasizes hands-on practice. BUMDes managers received training in creating visual and narrative content for social media, optimizing marketplaces such as Shopee and Tokopedia, and learning digital business management practices. Successful models like BUMDes Oeltuah demonstrate that intensive training can significantly improve managers' understanding and capabilities. The outcomes include enhanced skills in content creation, social media and online store management, as well as increased product visibility and sales. Furthermore, a digital mindset was cultivated, serving as a foundation for business sustainability. A comprehensive digital strategy, combined with ongoing training, is expected to strengthen the marketing of BUMDes products while also supporting rural economic development and achieving the Village SDGs goals.